2018
DOI: 10.1177/0268355518762824
|View full text |Cite
|
Sign up to set email alerts
|

Design and evaluation of the psychometric properties of a self-questionnaire on patient adherence to wearing elastic compression stockings

Abstract: Background Patients' adherence to elastic compression stockings is difficult to evaluate, and therefore we create a short self-questionnaire and validate its psychometric properties. Methods We reduce the questions with Varimed rotation analysis, evaluate its internal consistency using Cronbach's alpha test and its external validity by comparison to electronic thermic captors. Receiver operating characteristic (ROC) analysis was used to determine a threshold and determine its sensitivity and specificity. Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 4 publications
0
14
0
Order By: Relevance
“…Included studies present variable, and at times, conflicting descriptions of adherence, which are subject to interrelated concepts of the definition, measurement, and rate. Fourteen studies 9 , 38 , 41 , 42 , 44 , 61 , 63 , 68–74 considered adherence a primary outcome measure where the remainder discussed adherence as a secondary outcome measure or as a point of discussion. Thirty studies reported a numerical adherence rate as an outcome of a study.…”
Section: Resultsmentioning
confidence: 99%
“…Included studies present variable, and at times, conflicting descriptions of adherence, which are subject to interrelated concepts of the definition, measurement, and rate. Fourteen studies 9 , 38 , 41 , 42 , 44 , 61 , 63 , 68–74 considered adherence a primary outcome measure where the remainder discussed adherence as a secondary outcome measure or as a point of discussion. Thirty studies reported a numerical adherence rate as an outcome of a study.…”
Section: Resultsmentioning
confidence: 99%
“…Allaert developed a validated, short, selfadministered questionnaire to evaluate the patients' adherence to the GECS treatment. Physicians and nurses should use this suitable tool to assess patients' compliance with GECS in their day-to-day practice [28]. In the future, the methods for measuring compliance should also be unified, and medical staff should pay attention to the evaluation of patients' compliance.…”
Section: Plos Onementioning
confidence: 99%
“…Vulnerable skin can easily be injured if the stockings are inappropriately worn, as elderly individuals often have di culty wearing compression stockings. 14 Therefore, this study focused on vibration therapy as care methods using devices may reduce the need for additional manpower. Previous experiments showed that vibration effectively reduced upper limb lymphedema when provided as an additional care for simple lymphatic drainage 15 and improved lower limb transcutaneous oxygen tension during hemodialysis.…”
Section: Introductionmentioning
confidence: 99%